Price to book value, price to sales multiples and stock price; evidence from Nigerian listed firms - Shittu, I.; Che Ahmad, Ayoib; Ishak, Zuaini (Akademia Baru, 2016)
Valuation of company stock is a significant aspect of investment decision making.Investment analyst’s usually value stocks of companies for investors that wants to buy or sell stocks.One of the methods of valuing such is through equity valuation multiples.EVMs are practically used by security and investment analysts to value stock prices. However, little is known on empirical perspective of equity value multiples and stock price especially in emerging markets. This study investigated the influence of price to book value and price to sales multiples and stock price of selected firms in Nigeria. The study utilized data from 100 randomly selected listed firms in the Nigerian Stock Exchange.The research covered the period of 2009 to 2013. A random effect estimation model was used to estimate the regression.The result reveals significant positive relationship between, price to book value, price to sales multiples and the stock price.The implication of the positive relationship between the dependent and the independent variables implies that, P/B, and P/S, are significantly and positively associated to stock price.While the implication for low R2 is that, stock prices are not explained only by P/B and P/S multiples but by mixture of several variables.